Strategi Mauruts Tirkah Berdasarkan Hukum Adat di Provinsi Jambi - Irfanto, Nurwahyu; Apriani, Yani; Ramadhan, Alif Dzikra; Sari, Alvio Nita; Syamsiah, Syamsiah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This research discusses the strategy of distributing inheritance (tirkah) based on customary law in Jambi Province, which combines Malay traditional values with the principles of Islamic law. In Jambi Malay society, the division of inheritance is based on the philosophy of “Adat Bersendi Syara‘, Syara’ Bersendi Kitabullah”, which is the main guide to maintaining justice and social harmony. The process of division is usually carried out through deliberation involving family members, traditional leaders and ulama to reach consensus, while ensuring that individual rights are respected in accordance with customary law and Islamic teachings. This research identifies two main approaches to inheritance distribution: the collective system and the individual system. The collective system is applied to certain types of assets such as land and houses that are inherited jointly, while the individual system is applied to movable assets such as jewellery and vehicles. In this process, the Jambi Malay Customary Institution plays a key role as an arbiter to resolve inheritance conflicts while preserving traditional values. The results show that the division of inheritance in Jambi faces challenges, such as the influence of modernization and potential conflicts with formal law. Therefore, several strategies are proposed, including strengthening the role of customary institutions, organizing customary education, involving religious leaders, as well as facilitating deliberation to ensure this tradition remains sustainable.